2014
DOI: 10.1109/tbme.2014.2313226
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy Drug Scheduling for the Induction Treatment of Patients With Acute Myeloid Leukemia

Abstract: Leukemia is an immediately life-threatening cancer wherein immature blood cells are overproduced, accumulate in the bone marrow (BM) and blood and causes immune and blood system failure. Treatment with chemotherapy can be intensive or nonintensive and can also be life-threatening since only relatively few patient-specific and leukemia-specific factors are considered in current protocols. We have already presented a mathematical model for one intensive chemotherapy cycle with intravenous (i.v.) daunorubicin (DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 22 publications
0
20
0
1
Order By: Relevance
“…This tool also has the potential to evaluate clonal models of leukaemogenesis [4,6,39] in order to better understand the pathogenesis of disease. In the context of CCS drug dosage and scheduling, the PBM could give a narrower window of action than what is currently used in treatment regimens, thereby limiting drug toxicity yet improving efficacy [8,7]. Drugs, such as small molecule inhibitors, currently being tested that specifically target leukaemia subclones (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This tool also has the potential to evaluate clonal models of leukaemogenesis [4,6,39] in order to better understand the pathogenesis of disease. In the context of CCS drug dosage and scheduling, the PBM could give a narrower window of action than what is currently used in treatment regimens, thereby limiting drug toxicity yet improving efficacy [8,7]. Drugs, such as small molecule inhibitors, currently being tested that specifically target leukaemia subclones (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that assessment of proliferation kinetics and cellcycle times in AML may provide optimized chemotherapy protocols in order to improve tumour cell kill yet minimize toxicity for the patient [7,8]. Defining the changes that occur in the cell cycle is central to these optimized treatment protocols since many chemotherapeutic drugs are cell-cycle phase-specific and heterogeneity of patient responses may be broadly defined in terms of cell-cycle phase distributions and timings [9].…”
Section: Introductionmentioning
confidence: 99%
“…The model showed a good trade-off between capturing the important aspects of the dynamics, containing a moderate number of identifiable model parameters, and being applicable for different cytostatic drugs. It has become the gold-standard model in this field with different PK and population-based modifications to topotecan [21], to daunorubicin [22], to a combination therapy of Ara-C (low-dose), etoposide and daunorubicin in the induction treatment for AML [8], to a physiologically based PK model for the induction therapy of AML patients with daunorubicin and Ara-C (low-dose) [23], to a combination therapy of carboplatin, etoposide and thiotepa [24], to paclitaxel [10], to an individual-based approach [25], and to drug specific optimisations [9]. The model assumes a clustering of cells in compartments with identical properties.…”
Section: Methodsmentioning
confidence: 99%
“…8 In this section, each model will be embedded into a PK/PD model of chemotherapy delivery in leukemia 20 and tested for its sensitivity to chemotherapy (as captured by the chemotherapy drug effect parameters k D, S and k D, G for S and G1 phases respectively in CCP-ODE-PD,…”
Section: Analysis Under Chemotherapy Treatment Setting the Grounds Fomentioning
confidence: 99%